THE ROLE OF SOCIAL VOLUNTEERS IN THE DEVELOPMENT OF RELIGIOUS SOCIAL SERVICE ORGANIZATIONS AT PPPA DAARUL QUR'AN BANDUNG - Intan Sopiah Resikawati; Yuce Sariningsih (Universitas Pasundan, 2019)
Social organizations or institutions cannot walk without money. The financial aspect is indeed very important and requires that the organization conduct fundraising practices so that institutional funding can be fulfilled, therefore the role of social volunteers in fundraising is also one that must be considered. Social volunteer fundraisers are one of several parts of other volunteers. Fundraisers are tasked with funding to assist the sustainability of social service organizations as well as existing programs. The purpose of this study is to illustrate how volunteers in carrying out their roles include their rights and obligations, identify what is potential and problems in voluntary practice, see how the foundation provides efforts to develop the role of volunteers themselves, also what volunteer implications in practice and also tourists volunteer for social welfare science. The research method used was a qualitative approach with the location of the research study at the PPPA Daqu institute in the city of Bandung. The research informants were volunteers who were fundraisers at Mall outlets and also volunteer coordinators as secondary informants. Data collection uses participant observation, in-depth interviews, and secondary data tracking. Data collection used in-depth interviews, participant observation, and secondary data tracking, the results of the study were analyzed qualitatively using coding and category analysis and data validity through data triangulation, member checking, and rich and thick description. The results of the research obtained are about how the wages volunteers receive and also about fundraising schools that are intended for volunteers in improving their skills and potential.